Pengaruh Literasi Digital Youtube Keagamaan Terhadap Pemahaman dan Kesadaran Beragama Siswa di SMPN 18 Kota Bengkulu - Nihi Asli; Suhirman Suhirman; Desy Eka Citra Dewi (UIN Fatmawati Sukarno Bengkulu, 2025)
This research is motivated by the explosion of information obtained from current digital literacy such as: YouTube, Instagram, Twitter and other sources. YouTube is a very young platform that can be accessed as a media for preaching and learning media in schools. This research aims to: 1. To find out whether there is an influence of religious YouTube digital literacy on students' understanding of religion at SMPN 18 Bengkulu City. 2. Find out whether there is an influence of religious YouTube digital literacy on students' religious awareness at SMPN 18 Bengkulu City. The type of research used is quantitative with an associative approach. The research instrument used was a questionnaire. The data analysis technique is hypothesis testing using simple linear regression, t test and coefficient of determination ((R2). Research results: (1) There is an influence of religious YouTube digital literacy on students' understanding of religion at SMPN 18 Bengkulu City as evidenced by the regression equation Y1 = 48.889 + 0.531 18 Bengkulu City as proven by the regression equation Y2 = 48.998+ 0.430